Объяснение:
[7х+4у=5
[3х+2у=3
[7х+4У=5
[-2*3х-2*2у=-2*3
[-6х-4у=-6
7х+4у-6х-4у=5-6
х=-1
3*(-1)+2у=3
-3+2у=3
2у=3+3
2у=6
у=3
(х,у)=(-1,3)
[7*(-1)+4*3=5
[3*(-1)+2*3=3
[5=5
[3=3
7х+4у=5
3х+2у=3|×2
-
6х+4у=6
7×(-1)+4у=5
4у=5+7=12
ответ: (-1;3)
Объяснение:
[7х+4у=5
[3х+2у=3
[7х+4У=5
[-2*3х-2*2у=-2*3
[7х+4у=5
[-6х-4у=-6
7х+4у-6х-4у=5-6
х=-1
3*(-1)+2у=3
-3+2у=3
2у=3+3
2у=6
у=3
(х,у)=(-1,3)
[7*(-1)+4*3=5
[3*(-1)+2*3=3
[5=5
[3=3
(х,у)=(-1,3)
7х+4у=5
3х+2у=3|×2
7х+4у=5
-
6х+4у=6
х=-1
7×(-1)+4у=5
4у=5+7=12
у=3
ответ: (-1;3)